Efficiency comparison of mixture formulations in the stabilisation/solidification of the loess silt contaminated with zinc in terms of mechanical properties - Lal, Agnieszka; Fronczyk, Joanna; Franus, Małgorzata (Budownictwo i Architektura / Civil and Architectural Engineering, 2023)
The effectiveness of various types of binders in stabilizing/solidifying (S/S) contaminated soils is strongly dependent on the type of soil and contaminants present. The literature abounds with studies of stabilisation/solidification of clayey soils, which provides a background for initial assumptions in design of the method application for contamination of this type of soil. However, studies on the stabilisation/solidification of loess silt contaminated with heavy metals are not available. Filling this deficiency is important in order to ensure the rapid adoption of the most effective remedies in case of contamination and their immediate implementation in the subsoil. This paper has enabled the determination of the most effective mixture among the examined for the remediation of loess silt contaminated with zinc in terms of compressive strength. Strengths were determined with the implementation of 30% Portland cement (2.63 MPa), 30% of fly ash-cement mixture (2.21 MPa), an incinerated sewage sludge ash-cement mixture (0.93 MPa) and mixtures in which cement was replaced by an MgO activator (0.18 MPa for fly ash and 0.63 MPa for incinerated sewage sludge ash). In addition, the determination of strength was carried out for samples containing a mixture of fly ash, activator and cement (0.26 MPa) and incinerated sewage sludge ash, activator and cement (0.26 MPa), with weight ratios of 5:4:1 respectively. In summary, fly ash and cement in a 2:1 ratio can be considered the most effective binding mix in terms of unconfined compressive strength increase.